2020
DOI: 10.1002/eap.2154
|View full text |Cite
|
Sign up to set email alerts
|

Tropical tree size–frequency distributions from airborne lidar

Abstract: In tropical rainforests, tree size and number density are influenced by disturbance history, soil, topography, climate, and biological factors that are difficult to predict without detailed and widespread forest inventory data. Here, we quantify tree size-frequency distributions over an old-growth wet tropical forest at the La Selva Biological Station in Costa Rica by using an individual tree crown (ITC) algorithm on airborne lidar measurements. The ITC provided tree height, crown area, the number of trees >10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…Our approach complements recent methods [23][24][25][26][27][28][29][30][31][32][33][34][35][36] as it (i) integrates already available information on tree geometry (captured in the leaf-tree matrix) and (ii) estimates the full range of size classes in tree size distributions. Tree size distributions can be used to derive different forest attributes (e.g., tree density or forest basal area) and allow us to estimate a forest's successional state or disturbances [50].…”
Section: Strengths and Limitations Of The Presented Approachmentioning
confidence: 98%
See 2 more Smart Citations
“…Our approach complements recent methods [23][24][25][26][27][28][29][30][31][32][33][34][35][36] as it (i) integrates already available information on tree geometry (captured in the leaf-tree matrix) and (ii) estimates the full range of size classes in tree size distributions. Tree size distributions can be used to derive different forest attributes (e.g., tree density or forest basal area) and allow us to estimate a forest's successional state or disturbances [50].…”
Section: Strengths and Limitations Of The Presented Approachmentioning
confidence: 98%
“…To improve the allometries, crown size relations can also be derived by tree crown detection algorithms based on lidar point clouds [32,33,52]. For example, Ferraz et al [33] reported tree and crown allometries based on detected single trees and their respective uncertainties. This approach requires high-resolution lidar point clouds, particularly for correctly detecting small-and mid-sized trees (with small crowns) in the understory where the lidar point density is normally lower.…”
Section: Strengths and Limitations Of The Presented Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of crown delineation papers assess proposed methods using field-collected stem data in which a single GPS point, representing the position of the basal stem, is used to indicate the position of each tree [15]. There is high confidence that this type of evaluation data represents individual trees, because tree stems are often easy to identify in the field.…”
Section: Evaluation Datamentioning
confidence: 99%
“…In addition, the increased availability of terrestrial laser scanning (TLS) and high-resolution, low-altitude unmanned aerial vehicle lidar could substantially increase the data availability and thus improve the overall quality of allometric equations and constrain the relative contribution of woody tissues to the total plant area (Calders et al, 2015;Stovall et al, 2018). Alternatively, techniques that extract individual tree crowns from lidar point clouds readily provide highly accurate local stem density and local size-frequency distributions (e.g., tree height or crown size; Ferraz et al, 2016Ferraz et al, , 2020. These distributions can be used to attribute DBH to individuals and generate initial conditions akin to forest inventory to the ED-2.2 model, and data-model fusion techniques that leverage the growing availability of data could reduce uncertainties on many model parameters, including allometry (F. J.…”
Section: 1029/2020jg005677mentioning
confidence: 99%